2004
DOI: 10.1158/1055-9965.epi-03-0026
|View full text |Cite
|
Sign up to set email alerts
|

Association of CYP17, CYP19, CYP1B1 , and COMT Polymorphisms with Serum and Urinary Sex Hormone Concentrations in Postmenopausal Women

Abstract: Women with high circulating estrogen concentrations have an increased risk of breast cancer; thus, it is important to understand factors, including genetic variability, that influence estrogen concentrations. Several genetic polymorphisms that may influence sex hormone concentrations have been identified, including CYP17 (5-untranslated region T3 C), CYP19 [intron 4 (TTTA) n ‫؍‬ 7-13 and a 3-bp deletion (؊3)], CYP1B1 (Val 432 Leu), and COMT (Val 108/158 Met). We examined associations between these polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
76
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(84 citation statements)
references
References 34 publications
7
76
1
Order By: Relevance
“…Our results for CYP17 add to the growing number of studies reporting little or no association for genetic control by this particular SNP and hormone levels [18,19,[30][31][32][33][34][35][36]. Similarly, there is little evidence that circulating hormone levels vary substantially by the CYP1B1 or COMT genotypes [18,19,35,36]; however, the relationship with urinary metabolites of estrogen has been more consistent with higher concentrations observed for the variant genotypes [19,37].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Our results for CYP17 add to the growing number of studies reporting little or no association for genetic control by this particular SNP and hormone levels [18,19,[30][31][32][33][34][35][36]. Similarly, there is little evidence that circulating hormone levels vary substantially by the CYP1B1 or COMT genotypes [18,19,35,36]; however, the relationship with urinary metabolites of estrogen has been more consistent with higher concentrations observed for the variant genotypes [19,37].…”
Section: Discussionsupporting
confidence: 72%
“…Similarly, there is little evidence that circulating hormone levels vary substantially by the CYP1B1 or COMT genotypes [18,19,35,36]; however, the relationship with urinary metabolites of estrogen has been more consistent with higher concentrations observed for the variant genotypes [19,37]. One reason for the lack of an observed effect may be due to the limited ability of most previous studies to look at polymorphisms for several genes or SNPs jointly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, PCOS women homozygous for short alleles had higher testosterone/ estradiol ratios, higher testosterone levels and higher LH/FSH ratios compared to women homozygous for long alleles [17], probably due to their reduced aromatase activity. Regarding CYP19(TTTA) 7 allele, significant associations with lower estrone, estrone sulphate and estradiol concentrations have been reported [24,25]. This allele has been also associated with lower sperm concentration and motility in normozoospermic and oligospermic men, due to potential impairment of the aromatase activity [21].…”
Section: Discussionmentioning
confidence: 99%
“…While no studies have directly tested this association, a few studies have shown that polymorphisms in certain genes that encode estrogen synthesis and metabolizing enzymes are associated with altered hormone levels [9][10][11][12][13][14][15]. Specifically, a polymorphism in CYPc17α has been associated with higher estradiol and progesterone levels [9], higher estradiol only in women of low body mass index (BMI) [15], higher estrone levels [14], and higher SHBG levels [13]. A polymorphism in CYP19 (aromatase) has been associated with lower estradiol [10,11] and estrone levels [10].…”
Section: Introductionmentioning
confidence: 99%